If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + 4) = 236 Reorder the terms: 4(4 + 5x) = 236 (4 * 4 + 5x * 4) = 236 (16 + 20x) = 236 Solving 16 + 20x = 236 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 20x = 236 + -16 Combine like terms: 16 + -16 = 0 0 + 20x = 236 + -16 20x = 236 + -16 Combine like terms: 236 + -16 = 220 20x = 220 Divide each side by '20'. x = 11 Simplifying x = 11
| 8t+48t+t^2= | | 2x^3-32x^2+78x=0 | | 2w-4=4 | | 7-3*2+6+3=35 | | 1.86=6.2a | | 25x^3-15x^4=5x^3 | | -30+5(x-2)=4x+7 | | 9-7x=42+(-4x) | | 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 | | 3x-7=3(x-3)+3 | | ln(x+5)=ln(x-4)-ln(x+4) | | a-1/2=2a-2/3 | | 4x+15x+6=3x-14 | | 19+20m+m^2= | | 24x+8x^2+2x^3=0 | | .4w-.3w+.4w=3 | | 3(2x-5)=5(x-4+x) |